2015
DOI: 10.15277/bjdvd.2015.046
|View full text |Cite
|
Sign up to set email alerts
|

Insulin treatment and longer diabetes duration both predict poorer glycaemic response to liraglutide treatment in type 2 diabetes: the Association of British Clinical Diabetologists Nationwide Liraglutide Audit

Abstract: Background: Liraglutide may be less effective in patients with more advanced type 2 diabetes. This study from the Association of British Clinical Diabetologists Nationwide Liraglutide Audit analysed changes in HbA1c of patients after 26 weeks of treatment with liraglutide 1.2 mg, stratified according to the intensity of their background diabetes therapy, or according to their duration of diabetes. Methods: Patients using liraglutide as add-on therapy were stratified for receipt to one, two or three oral antidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…These lower proportions could be explained by the high mean baseline HbA1c in our study, which has previously been identified as a significant predictor of achieving HbA1c targets in response to liraglutide [22]. Response may also be influenced by duration of diabetes; our results indicated a poorer response to the glycemic reduction and control targets with increased duration, a finding consistent with the Association of British Clinical Diabetologists Nationwide Liraglutide Audit [23]. …”
Section: Discussionsupporting
confidence: 87%
“…These lower proportions could be explained by the high mean baseline HbA1c in our study, which has previously been identified as a significant predictor of achieving HbA1c targets in response to liraglutide [22]. Response may also be influenced by duration of diabetes; our results indicated a poorer response to the glycemic reduction and control targets with increased duration, a finding consistent with the Association of British Clinical Diabetologists Nationwide Liraglutide Audit [23]. …”
Section: Discussionsupporting
confidence: 87%
“…Both clinical and demographic factors have been identified as potential predictors of response to therapy, including age at diagnosis, duration of diabetes, baseline insulin dose, baseline glycated haemoglobin (HbA1c), body mass index (BMI), lipid levels, renal function, sex, geographical region, and ethnicity 5‐9 . Particular concerns with regard to response to glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) have been duration of diabetes, glucose control and insulin dose, all of which, when greater, might suggest less islet β‐cell reserve or reduced function 10,11 . Furthermore, there is evidence to suggest a lower risk of hypoglycaemia in people with higher BMI, 12,13 so any advantage of GLP‐1RAs over insulin might then be ameliorated.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 , 8 , 9 Particular concerns with regard to response to glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) have been duration of diabetes, glucose control and insulin dose, all of which, when greater, might suggest less islet β‐cell reserve or reduced function. 10 , 11 Furthermore, there is evidence to suggest a lower risk of hypoglycaemia in people with higher BMI, 12 , 13 so any advantage of GLP‐1RAs over insulin might then be ameliorated.…”
Section: Introductionmentioning
confidence: 99%
“…One of the mechanisms through which GLP-1 RAs achieve glycemic control is stimulation of β-cell insulin secretion [89]; as such, it follows that GLP-1 RA treatment in patients with marked β-cell failure will not achieve sufficient insulin secretion, thereby reducing the efficacy of this approach in patients with more advanced disease. Indeed, studies have shown that longer duration of diabetes and severe insulin deficiency is associated with reduced efficacy of longer-acting GLP-1 RAs [9092], which is especially important in older adults who may have longstanding disease. With this in mind, the combination of a GLP-1 RA with basal insulin remains a logical approach to T2D treatment, based on the complementary effects of these two agents.…”
Section: Rationale For Combination Therapy Comprising Glp-1 Ras and Bmentioning
confidence: 99%